Psychometric properties of the Chinese version of quality of life in life-threatening illness-family carer version - Wei, Yitao; Xiao, Huimin; Wu, Hong; Yong, Binbin; Weng, Zhichao; Chen, Weiling (Frontiers in Psychology, 2022)
Background The Quality of Life (QOL) in Life-threatening Illness-Family Carer Version (QOLLTI-F) has been proven to be a brief, reliable, and valid instrument for measuring the caregivers’ QOL in western cultures. However, whether it is suitable to be used in Chinese culture is unclear. This study aimed to test the reliability and validity of the Chinese version of (QOLLTI-F-CV). Materials and methods A total of 202 family caregivers (FCs) of advanced cancer patients from Fujian Provincial hospice care center were investigated using the Chinese version of QOLLTI-F-CV from September 2019 to August 2020. The questionnaire was evaluated using an exploratory structural equation model. Its psychometric properties were examined in terms of factor structure, convergent validity, discriminant validity, internal consistency, and test–retest reliability. Results Differently from the seven-domain original QOLLTI-F, its Chinese version had only three domains including caregiver’s self-feelings, caregiver’s stress, and caregiver’s outlooks. The total variance explanation rate for the domains was 55.4%. The Chinese version fitted well with the structure model (χ2 = 153.932, df = 75, P < 0.001); its comparative fit index (CFI) was 0.971; Tucker–Lewis index was 0.954; and the root mean square error of approximation (RMSEA) was 0.072. The success rate of its convergent and discriminant validity calibration test was 100%. Its Cronbach’s alpha coefficient of the whole questionnaire and three domains was from 0.650 to 0.874, and test–retest reliability was 0.836. Conclusion The 3-domain QOLLTI-F-CV is a valid and reliable instrument for identifying QOL concerns of FCs of advanced cancer patients in China. The refactoring structure optimally matches Chinese culture and value system well.